Bergey's Manual® of Systematic Bacteriology Volume Two: The Proteobacteria, Part A Introductory Essays. (Springer US : Imprint: Springer, 2005)
Includes introductory chapters on classification of prokaryotes, the concept of bacterial species, numerical and polyphasic taxonomy, bacterial nomenclature and the etymology of prokaryotic names, nucleic acid probes and their application in environmental microbiology, culture collections, and the intellectual property of prokaryotes. The first Road Map to the prokaryotes is included as well as an overview of the phylogenetic backbone and taxonomic framework for prokaryotic systematics.